From Majorana Neutrino and Dark Neutrino 0 to Dark Spin Particles (Global Journal of Science Frontier Research, 2021)
In current theory of particle physics, the values of Casimir Operator, that is abbreviated to CO, of spin angular momentum for elementary particles are thought to be greater than zero. Both Majorana Neutrino and Majorana Antineutrino are all with CO . Now the above limited region of CO is enlarged, this paper assumes that for the particles, the values of CO are still positive; for the antiparcles, however, the values of CO are negative. In this point of view, something similar is expected to happen in the case of Majorana Neutrino and Majorana Antineutrino . The Majorana Neutrino would be still with CO and the Majorana Antineutrino would be with CO . Further, leading to the possible existence of the so-called Dark Neutrino, DN or is with CO that is the superposition of Majorana Neutrino and Majorana Antineutrino . And is the one-half spin fermion with zero-charge and zero-CO , which is a more neutral neutrino than Majorana neutrino.
Keywords: majorana neutrino; dark neutrino; casimir operator; particle; antiparticle; left-handed neutrino